Equations of rotational motion and their derivation

We have the equations of motion for a linear(or translational) motion as:

    \begin{align*} v &= u + at \\ v^2 &= u^2 + 2as \\ s &= ut + \frac{1}{2}at^2 \end{align*}

For the rotational motion, we replace v by \omega, u by \omega_0, s by \theta and a by \alpha in the above equations of motion. To know more about rotational motion, click here.

The equations of rotational motion become:

    \begin{align*} \omega &= \omega_0 + \alpha t \\ \omega^2 &= \omega_0^2 + 2\alpha \theta \\ \theta &= \omega_0 t + \frac{1}{2} \alpha t^2 \end{align*}

Here is the derivation of the rotational motion equation.

equations of rotational motion

1] Proof of the first equation of rotational motion

Consider a rigid body moving with constant angular acceleration ‘\alpha‘ such that its angular velocity reaches ‘\omega‘ from ‘\omega_0‘ in time ‘t‘ covering an angular displacement ‘\theta‘.

    \begin{align*}\alpha &= \frac{d\omega}{dt} \\ d\omega &= \alpha \,dt \\ \end{align*}

Integrating the above equation with the corresponding limit.

    \begin{align*}  \int_{\omega_0}^{\omega} d\omega &= \alpha \int_{0}^{t} dt  \\ [\omega]_{\omega_0}^{\omega} &= \alpha [t]_{0}^{t}  \\ \omega - \omega_{0} &= \alpha (t-0) \\ \omega - \omega_0 &= \alpha t \end{align*}

    \[ \boxed{\omega = \omega_0 + \alpha t} \]

2] Proof of second equation of rotational motion

Let’s start with the angular velocity to prove another equation.

    \begin{align*} \omega &= \frac{d\theta}{dt} \\  d\theta &= \omega \, dt \\  \end{align*}

Integrating the above equation with the corresponding limit.

    \begin{align*} \int_{0}^{\theta} d\theta &= \int_{0}^{t} \omega \, dt \\ \int_{0}^{\theta} d\theta &= \int_{0}^{t} (\omega_0 + \alpha t)dt \\ \int_{0}^{\theta} d\theta &= \int_{0}^{t} \omega_0 \, dt + \int_{0}^{t}  \alpha t \, dt \\ \int_{0}^{\theta} d\theta &= \omega_0 \int_{0}^{t} dt + \alpha \int_{0}^{t}  t \, dt \\ [\theta]_{0}^{\theta} &= \omega_0 [t]_{0}^{t} + \alpha \left[\frac{t^2}{2}\right]_{0}^{t} \\ \end{align*}

    \[ \boxed{\theta = \omega_{0} t + \frac{1}{2}\alpha t^2 }\]

3] Proof of third equation of rotational motion

We know, that angular acceleration is the rate of change of angular velocity. So,

    \begin{align*} \alpha &= \frac{d\omega}{dt} \\  \alpha &= \frac{d\omega}{d\theta} \frac{d\theta}{dt} \\ \alpha &= \frac{d\omega}{d\theta} \omega \\ \alpha &= \omega \frac{d\omega}{d\theta}  \\  \end{align*}


    \begin{align*}\alpha \, d\theta&= \omega \, d\omega  \\  \end{align*}

Integrating within a corresponding limit,

    \begin{align*} \alpha \int_{0}^{\theta} d\theta &= \int_{\omega_0}^{\omega}\omega \, d\omega \\  \alpha \left[ \theta\right ]{0}^{\theta} &= \left[\frac{\omega^2}{2}\right]{\omega_0}^{\omega}\\ \alpha \theta &= \frac{1}{2}(\omega^2-\omega_0)\\ 2\alpha \theta &= \omega^2 - \omega_0 \\\end{align*}

    \[  \boxed{\omega^2 = \omega_0 + 2 \alpha \theta} \]

These three equations can define the rotational motion of a rigid body.

Also, check out the table that shows the quantities used in both translational as well as rotational motion.

Sharing is Caring

Leave a Comment

Your email address will not be published.